Retrospective Study of Conservative Management of Appendicular Lump - Adhikari, Bimarsh (Journal of Nepalgunj Medical College, 2017)
Introduction: Appendicitis is very common surgical emergency and incidence of appendicular lump is about 2-6%. There are different approaches for management of appendicular lump among which most common and widely accepted approach is managing lump conservatively with interval appendicectomy 6 weeks after resolution of inflammation. The aim of the study is to evaluate the efficacy of the conservative management in appendicular lump.Materials and methods: Retrospective study of the 43 patients admitted with a diagnosis of appendicular lump from March 2015 to February 2016 at Nepalgunj medical college, Nepalgunj were carried out.Result: Out of 204 patients of appendicitis 43(21.07%) patients were found to have appendicular lump. Age ranged from 6 to 81yrs old. Appendicitis was found to be common at the age range of 21 to 30 years (44.18%).patient reported after 3 to 8 days of Onset of symptoms but most of the patients reported at 5 to 6 days of onset of symptoms. Among 43 patients, 40 patients (93.01%) managed successfully with conservative management. Only three patients (6.97%) developed complications. Out of these conservatively managed, 18(41.86%) underwent interval appendicectomy, 19(44.18%) patients lost to follow up,3(6.97%) had recurrent appendicitis.Conclusion: Our study concluded that most of the appendicular lumps can be managed conservatively with few complications, which can be managed with immediate intervention.